2008
DOI: 10.1117/12.799668
|View full text |Cite
|
Sign up to set email alerts
|

The source of carbon contamination for EUV mask production

Abstract: As the semiconductor industry requires lithography suitable for 32-nm node, extreme ultraviolet lithography (EUVL) has the potential to provide this capability for the mass fabrication of semiconductor devices. But because an extreme ultraviolet (EUV) lithography exposure system is operated in vacuum, during irradiation by EUV light, hydrocarbons are decomposed in vacuum 1-3 , for example, by the outgassing from EUV mask, and contaminate the surface of imaging optics which is coated with Mo/Si multilayers with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Given that carbon readily absorbs EUV radiations at 13.5nm, it reduces the reflectivity of Mo/Si multilayer (ML) and degrades exposure uniformity, heavily effecting Critical Dimension (CD) control [17]. Various dry and wet cleaning methods have been evaluated for carbon contamination removal [15,[18][19][20][21] however, damage to the multilayer from use of these removal methods has not been documented in the respective literature. Carbon removal is essential, but preserving Ru layer integrity while doing so is imperative.…”
Section: Carbon Contaminationmentioning
confidence: 99%
“…Given that carbon readily absorbs EUV radiations at 13.5nm, it reduces the reflectivity of Mo/Si multilayer (ML) and degrades exposure uniformity, heavily effecting Critical Dimension (CD) control [17]. Various dry and wet cleaning methods have been evaluated for carbon contamination removal [15,[18][19][20][21] however, damage to the multilayer from use of these removal methods has not been documented in the respective literature. Carbon removal is essential, but preserving Ru layer integrity while doing so is imperative.…”
Section: Carbon Contaminationmentioning
confidence: 99%
“…Consequently, wet cleaning methods, which do not require intricate equipment and induce less damage to photomask patterns and thin films compared to physical and dry cleaning methods, are currently widely employed. According to Kim et al and Nii et al, wet cleaning with SPM and SC-1 is commonly conducted in a temperature range of 80 °C-100 °C [17,18]. Choi et al revealed that a cleaning loss of 2 nm in the ARC layer thickness of a Ta-based EUV photomask occurred after 30 cycles of high temperature SPM cleaning and 20 cycles of EUV exposure [19].…”
Section: Introductionmentioning
confidence: 99%